On the Measure of Quantum Correlations - Majewski, Wladyslaw Adam (Communications in Mathematics and Applications, 2023)
In this paper, we present novel qualities of the measure of noncommutative (so quantum) correlations for general quantum systems. In other words, the fundamental difference between classical and non-commutative probability will be studied. In particular, we introduce the notion of coefficient of quantum correlations \(d(ω, A)\). The main theorem says that there are quantum correlations if and only if \(d(ω, A) > 0\). Our presentation is done within \(C^*\)-algebraic description of Quantum Theory.
Keywords: Quantum correlations; C*-algebra; Decomposition theory